Urban Forest Fires in Copacabana (Rio de Janeiro): Remote Sensing and Social Analysis - Sabino, Hullysses; Milagres da Rocha Mendonça , Fernanda; Menezes, Juliana (Anuário do Instituto de Geociências, 2025)
Fires aggravate the ecological imbalance by destroying fauna and flora, particularly when they occur in urban forest. In this environmental has the vegetation distinguished by environmental stress and the remnants fragmentation. Urban forest fires also affect society, which is touched and reacts in different ways. In light of the legally protected forest remnants vulnerability that are frequently targeted by fires, the environmental preservation units and forest fragments in the Copacabana neighborhood (Rio de Janeiro) were the subject of this study. Newspapers and social media reseach was performed in order to describe the fire cases occurred and their social repercussions. Forest fires were identified in four areas: São João Hill, Cabritos Hill, Arpoador and Pavão-Pavãozinho Hill. The first three are legally protected. The events ocurred in 2010, 2012, 2021, 2022 and 2024, some years with more than one fire episode. Satellite images from Sentinel 2, Landsat 8 and 9, Amazônia 1 and CBERS S4A and the satellites of the BDQueimadas geoportal of the National Institute for Space Research were consulted, but none succeeded in capturing the occurrence of the fires. Patterns of social response and behavior were identified and described. It is expected that this study will provide information to decision makers regarding the conservation of urban forests and social management in the Copacabana neighborhood.